An Analysis of Conversational Implicature in Antigone Drama Manuscript - Cahyati, Dani Puji, Drs. Agus Wijayanto M.A., Ph.D (2017)
This research aimed to classify the types of conversational implicature and the reasons of using implicature in utterances that used by the characters in Antigone drama. The researcher used descriptive qualitative method to analyze the data. All data were collected and analyzed based on the Thomas (1995) theory of conversational implicature for classifying the types of conversational implicatures and Grice (1975) theory of cooperative principles for analyzing maxims violation in Antigone drama. The result of the study showed there are 60 data containing the types of conversational implicatures. generalized conversational implicature presents the dominant frequency more than particularized conversational implicature. There are 58 data of violation maxims on generalized conversational implicature (96%). Those are 26 data on violation maxim of quality (43%); 20 data on violation maxim of quantity (26%); 12 data on violation maxim of relevance (Relation) (20%) and 4 data on violation maxim of manner (7%). Some others data, there are 2 data of violation maxims on particularized conversational implicature (4%). And the next rank is particularized conversational implicature. Those are 1 datum on violation maxim of relevance (Relation) (2%) and 1 datum on violation maxim of manner (2%). In addition, the researcher also found some reasons of using implicatures (teasing, refusing, hurting, apologizing, convincing, showing vanity, wishing, caring (sympathy), reminding, informing, guessing, self-defending, angrying, disappointment, ignorance and informing).